A novel high-throughput screen identifies phenazine-1-carboxylic acid as an inhibitor of African swine fever virus replication in primary porcine alveolar macrophages - Jing Lan; Rui Luo; Di Liu; Changxing Qi; Xin Song; Zhanhao Lu; Ruojia Huang; Yuying Yang; Yuan Sun; Yonghui Zhang; Tao Wang; Hua-Ji Qiu (Veterinary Research)
Abstract African swine fever (ASF), caused by African swine fever virus (ASFV), has resulted in significant economic impacts on the global swine industry. Currently, there is no safe and effective commercial vaccine available for ASFV. Thus, the development of effective and readily available therapeutics for ASF is urgently needed. To conduct high-throughput screening (HTS) for anti-ASFV drugs, we initially developed a recombinant dual-reporter virus (rASFV-Gluc/EGFP) using the virulent strain ASFV HLJ/18 (ASFV-WT). The enhanced green fluorescent protein (EGFP)- and Gaussia luciferase (Gluc)-encoding genes were incorporated downstream of the ASFV MGF300-4L gene without disrupting viral genes. The growth kinetics, hemadsorption, and transmission electron microscopy analysis of rASFV-Gluc/EGFP in primary porcine alveolar macrophages (PAMs) revealed that rASFV-Gluc/EGFP exhibits similar biological characteristics to ASFV-WT. Furthermore, analysis of Gluc activities, fluorescence, and next-generation sequencing indicated that rASFV-Gluc/EGFP maintains good genetic stability after 20 consecutive passages in PAMs. Using the HTS platform established with rASFV-Gluc/EGFP, we screened and identified phenazine-1-carboxylic acid (PCA) as an effective inhibitor of ASFV replication from 246 small molecule compounds in PAMs. Importantly, PCA was found to reduce ASFV replication by as much as 100-fold at a concentration of 25 μM. Overall, this study suggests that rASFV-Gluc/EGFP is suitable for rapid screening of anti-ASFV drugs. Importantly, we showed that PCA has significant anti-ASFV activity in PAMs.